TOWARDS A VERY BRITISH VERSION OF THE CULTURE WARS populism, social. - Bonnet, Alma-Pierre; Espiet-Kilty, Raphaële ([S.l.] : ROUTLEDGE, 2024)
"This book examines the emergence and the political use of what has come to be known as "culture wars" in the United Kingdom. Adopting multidisciplinary perspectives, it investigates the ways in which cultural identities are used for political ends. The book bridges the conceptual and theoretical gap in fully understanding so-called "culture wars" in a British context; as such, it envisages debates as part of a larger political project to gain popular support by tapping into voters' sense of neglect by the political elite. Applying the concept of "national populism" as a binding conceptual framework for the book, a prestigious panel of international experts offer thorough analyses to show that not enough attention is being paid to what may be considered as an "escalation" of culture wars, and to how divisions have been accentuated by political elites to deliberately exacerbate them. This book will be of key interest to scholars, students and readers in British politics, populism studies, party politics, Conservative party politics and more broadly to European and Comparative politics"--
Keywords: Communication in politics -- Great Britain; Mass media and culture -- Great Britain; Campaign debates -- Great Britain; Elite (Social sciences) -- Political activity -- Great Britain; Culture conflict -- Political aspects -- Great Britain; Cultural pluralism -- Political aspects -- Great Britain; Populism -- Great Britain; Great Britain -- Politics and government -- 2007-